PO15 Chemical composition of essential oils from Cholupa, Gulupa, Curuba y Badea for virtual simulation - Castañeda, Jhon Fredy; MORALES LOAIZA, Aldemar; Sánchez-Ramirez, Nina María; Ríos-Bustos, Maira Jenifer; Montealegre, Yeimis Johana; Huertas, Jhonathan Andrés; Bahamón Useche, Andrés Ronaldo (Revista Productos Naturales, 2025)
Colombia is the country with the greatest diversity of plants belonging to the Passifloraceae family, with an estimated 170 species (Ocampo & Merlín, 2014). Species of this family, which are very important for the Colombian fruit sector, are cultivated in the department of Huila, mainly passion fruit (Passiflora edulis var. flavicarpa Degener), cholupa (P. maliformis L.), granadilla (P. ligularis Juss), and gulupa (P. edulis var. edulis Sims), among others. In this work, a comparative study of the yield and chemical composition of essential oils (EOs) of Passiflora maliformis L., Passiflora edulis var. edulis, Passiflora tripartita var. mollísima
Keywords: Passionflowers, essential oils, virtual simulation